(untitled) (Journal of Engineering, 2018)
Global Navigation Satellite System (GNSS) is considered to be one of the most crucial tools for different applications, i.e. transportation, geographic information systems, mobile satellite communications, and others. Without a doubt, the GNSS has been widely employed for different scientific applications, such as land surveying, mapping, and precise monitoring for huge structures, etc. Thus, an intense competitive has appeared between companies which produce geodetic GNSS hardware devices to meet all the requirements of GNSS communities. This study aims to assess the performance of different GNSS receivers to provide reliable positions. In this study, three different receivers, which are produced by different manufacturers, were fixed to form a triangle. Simultaneous observations were made in static mode (2.5 to 3 hours). This observation technique was carried out three times by changing the location of receivers in each time to ensure that three receivers observed each station three times. To evaluate the performance of each receiver, OPUS web-based processing software and TOPCON TOOLS were used to process the raw GNSS observations. The distances between adjacent stations were computed for each observation and compared to standard distances, which were measured using a total station. Furthermore, the internal angles were also computed and compared to those measured by Total Stations. The results showed that some calculated distances are closer to the corresponding distances measured by the total station. This indicates that the receivers involved in the composition of these distances are the most accurate.